A new route to graphene starting from heavily ozonized fullerenes: Part 3 – an electron spin resonance study. Issue 3 (3rd March 2016) - Cataldo, Franco; Putz, Mihai V.; Ursini, Ornella; Angelini, Giancarlo; Garcia-Hernandez, D. Anibal; Manchado, Arturo
ABSTRACT: It is shown that graphite oxide (GO) and both heavily ozonized C60 and C70 fullerenes, known as "fullerene ozopolymers, " are paramagnetic materials with a very strong electron spin resonance (ESR) signal at room temperature. When thermally annealed, the paramagnetic centers are gradually lost in large part. This occurs at 350°C in the case of GO, while for fullerene ozopolymers, a higher temperature is required, reaching the same results in the end. The half-width of ESR signal is linked to the distribution of paramagnetic centers. Once again, striking analogies were found in the half-width of the ESR signal measured on GO and fullerene ozopolymers, at least in the temperature range of 25–450°C. Similarly, the same g-factor values, which are diagnostic for understanding the chemical nature of paramagnetic centers, were found on both GO and fullerene ozopolymers in all ranges of temperature considered.